The Implementation of Drug Information Services for Patients Using Antibiotics in Palanro Puskesmas Mallusetasi District, Barru Recency - Murniati, Murniati; Jufri, Alfina (Jurnal Farmasi Sandi Karsa, 2021)
This research has been done with the aim to know Description of the implementation of drug information for patients using antibiotics at Palanro public health center Mallusitasi distric Barru regency. This research used descriptive method by using questionnaire as an instrument for collecting data that has Been given to 100 respondents all at once involved to redeem prescription at Palanro public health center Mallusitasi district Barru regency. Data processing was done by colleting data, tabulating, scoring with tabular form. From the result of this research, it can be inferred that description of the implementation of drug informations for patients using antibiotics at Palanro public health center Mallusitasi district, Barru regency are 30,78%, it’s mean that implementation in low cathegory (0-33,3%).